Simultaneous Determination of 12 Marker Components in Yeonkyopaedok-san Using HPLC–PDA and LC–MS/MS - Chang-Seob Seo; Hyeun-Kyoo Shin (Applied Sciences, 2020)
Yeonkyopaedok-san is a traditional Korean medicine used in the early treatment of boils. In the present study, its 12 marker components for quality control were determined using high-performance liquid chromatography (HPLC) with photodiode array detection and ultra-performance liquid chromatography−mass spectrometry with tandem mass spectrometry (UPLC−MS/MS). The investigated 12 marker components of Yeonkyopaedok-san were as follows: 3-caffeoylquinic acid, cimifugin 7-glucoside, liquiritin apioside, ferulic acid, narirutin, 5-O-methylvisammioside, naringin, neohesperidin, oxypeucedanin hydrate, arctigenin, glycyrrhizic acid, and 6-gingerol. The analytical column used for the separation of the 12 marker analytes in Yeonkyopaedok-san was a Waters SunFire C18 column (4.6 mm × 250 mm, 5 μm). The two mobile phases used were 0.1% (v/v) aqueous formic acid and 0.1% (v/v) formic acid in acetonitrile. In the UPLC−MS/MS analysis, all components were separated using a Waters ACQUITY UPLC BEH C18 column (2.1 mm × 100 mm, 1.7 μm). The two mobile phases used were 0.1% (v/v) aqueous formic acid and acetonitrile. The coefficient of determination of the calibration curves in both analysis systems showed good linearity (>0.99). The amounts of the 12 marker components in Yeonkyopaedok-san determined using HPLC−photodiode array detection and UPLC−MS/MS analyses were found to be 0.14−9.00 mg/g and 2.35−853.11 μg/g, respectively.